The Pathology of Hyperthyroidism - LiVolsi, Virginia A.; Baloch, Zubair W. (Frontiers in Endocrinology, 2018)
This article reviews those pathologic lesions which are associated with clinical and/or biochemical hyperthyroidism. Beginning with the descriptive pathology of classical Graves’ disease and the less common toxic nodular goiter and hyper-functioning thyroid nodules, this paper describes the effects of non-thyroidal hormones, glandular function (including pituitary and hypothalamic lesions), ectopic production of thyroid stimulating proteins by non-thyroidal neoplasms, exogenous drug reactions causing hyper-function and finally conditions associated with a mechanic- destructive cause of hyperthyroidism.